My beautiful birds - Del Rizzo, Suzanne (Toronto, Ontario : Pajama Press Inc., 2017)
Behind Sami, the Syrian skyline is full of smoke. The boy follows his family and all his neighbours in a long line, as they trudge through the sands and hills to escape the bombs that have destroyed their homes. But all Sami can think of is his pet pigeons--will they escape too? When they reach a refugee camp and are safe at last, everyone settles into the tent city. But though the children start to play and go to school again, Sami can't join in. When he is given paper and paint, all he can do is smear his painting with black. He can't forget his birds and what his family has left behind. One day a canary, a dove, and a rose finch fly into the camp. They flutter around Sami and settle on his outstretched arms. For Sami it is one step in a long healing process at last.
Keywords: Refugees -- Syria -- Juvenile fiction; Refugee camps -- Juvenile fiction; Birds -- Juvenile fiction; Art -- Psychological aspects -- Juvenile fiction; Art therapy for children -- Juvenile fiction; Picture books; Refugees -- Syria -- Fiction; Refugee camps -- Fiction; Birds -- Fiction; Refugee camps -- Fiction; Refugees -- Syria -- Fiction; Birds -- Fiction